“. . .It’s Just the Barriers That Can Be So Vast and Different”: Domestic Violence Advocates’ Perceived Barriers for Service Across Survivor Subpopulations - Reed, Shon M. (Crime & delinquency, 2024)
Intimate partner violence (IPV) is a serious issue that impacts people of all demographics. Despite its pervasiveness, IPV survivors often seek help from informal sources of help over formal help sources, such as victim service providers (VSPs). This can prove to be an issue as VSPs provide crucial services that assist survivors in exiting abusive relationships. Using content analysis, the current study assesses interview data with 16 victim advocates to highlight barriers experienced by IPV survivors when seeking help. Analyses indicate specific barriers located at the organizational, community, and individual levels of society. Further, barriers specific to heterosexual men and LGBTQIA survivors were identified. Future avenues for research and policy recommendations are provided after a presentation of the findings.